Research Problem and Selection of Topic - Baloch, Tahir Hakeem; Sadiq, Muhammad; Rauf, Abdul (sourcecoder, 2024)
Every research starts with a research problem and becomes the first step of the research which is followed by extensive literature review, expertise and knowledge of researcher and significance of the topic. The task of defining and formulating the research problem is a step of greatest importance in the entire research process. This study aims at discussing and defining and formulating a research problem and evaluating the process of selection of research topic as well. Moreover, the role of researcher in the process of formulating a problem and the selection of topic has also been discussed thoroughly in this article.